Criticism of the Qur'an’s Discretion in Expressing Untruths - Mostafa Karimi; Hamidreza Moghimi Ardakani (آموزه‌های قرآنی)
Scholars know the use of lies to achieve more important benefits. Is it even possible to consider the possibility of an untrue statement to be reasonable because of the discretion of the word of the wise God? If this possibility is reasonable about the words of God and its non-occurrence is not proven, the authenticity of the Qur'an will be questioned. As a result, Qur'anic guidance cannot be used conclusively in epistemological fields. The present article, first by rational method and then by analyzing the verses of the Qur'an, has ruled out the possibility of finding a way to induce a false interest in the Holy Qur'an. Some of the reasons given for rejecting this claim are insufficient, but an attempt has been made to correct and complete the presented arguments and to prove the claim with sufficient rational proof, and then to emphasize the validity of this claim by quoting the Qur'an. The result is that the Holy Qur'an uses good intentions such as the level of understanding of the audience, speaking the language of the people, and observing artistic issues, but it does not require the induction of unprofitable interests, and none of the examples presented as white lies testify to this.